Pancreatic Progenitors: There and Back Again. (January 2019) - Domínguez-Bendala, Juan; Qadir, Mirza Muhammad Fahd; Pastori, Ricardo Luis
Abstract : Adult pancreatic regeneration is one of the most contentious topics in modern biology. The long-held view that the islets of Langerhans can be replenished throughout adult life through the reactivation of ductal progenitor cells has been replaced over the past decade by the now prevailing notion that regeneration does not involve progenitors and occurs only through the duplication of pre-existing mature cells. Here we dissect the limitations of lineage tracing (LT) to draw categorical conclusions about pancreatic regeneration, especially in view of emerging evidence that traditional lineages are less homogeneous and cell fates more dynamic than previously thought. This new evidence further suggests that the two competing hypotheses about regeneration are not mutually exclusive. Highlights: Conventional views on pancreatic regeneration, long thought to involve the reactivation of a duct-based embryonic program, have been challenged over the past decade by LT studies, which suggest instead the self-duplication of mature cells. However, single-cell resolution analyses have blurred lineage barriers and suggest a high degree of developmental heterogeneity within each pancreatic compartment. Evidence for dynamic fate plasticity and facultative dedifferentiation calls into question the validity of LT findings. Conflicting views may be reconciled in a model where multiple layered regeneration mechanisms follow a specific activation sequence depending on the extent of the damage. Novel organotypic culture and transplantation techniques herald a new era of human-centric studies on pancreatic regeneration, circumventing the limitations of the mouse model.